Factors influencing the development of leadership skills of Kazakhstani youth - Yermekbayeva, M.K. (Ye.A.Buketov Karaganda State University Publ., 2014)
Present time there has been increasing interest in the topic of leadership skills development of Kazakhstani youth. The author considers globalization and set Strategy «Kazakhstan – 2050» as the most motivating factors to youth’s skills development. The researcher has conducted qualitative research in the form of in-depth interviews to examining the factors that influence the development of leadership skills of Kazakhstani youth. These are the education system represented by teachers and business involvement in youth’s life. Based on the findings, the researcher has defined the skills gap in the context of demotivation of education and business to be involved in every day youth’s life to cultivate values and leadership skills.
Қазақстан жастарының көшбасшылық дағдысы дамуына ыкпал етушi факторлар
Факторы, влияющие на развитие лидерских навыков казахстанской молодежи
Keywords: Strategy; globalization; Kazakhstani youth; education; business sector; development; motivating factors; values; skills; youth problems